The Role of Human Resource Management (HRM) Strategy in Increasing Employee Work Productivity - Anderi Anderi; Dhenny Asmarazisa; Catur Fatchu Ukhriyawati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the role of Human Resource Management (HRM) strategies in improving employee productivity. The research method used is a quantitative method with a descriptive-verification approach. Data were collected through questionnaires distributed to randomly selected respondents and analyzed using multiple linear regression analysis techniques to examine the influence of HRM strategy variables on work productivity. HRM strategy variables include human resource planning, recruitment and selection, training and development, compensation, and performance appraisal. The results show that HRM strategies have a positive and significant effect on employee productivity. Among the dimensions studied, training and development and compensation systems have the greatest contribution to increasing productivity. These findings emphasize the importance of implementing effective and sustainable HRM strategies to support individual and organizational performance. This study provides practical implications for company management in formulating more targeted human resource management strategies oriented towards increasing productivity.